Hubungan Asupan Asam Folat, Zat Besi dan Status Ekonomi Keluarga dengan Berat Bayi Lahir - Faradina Aghadiati (Jurnal Kesehatan Terpadu (Integrated Health Journal), 2020)
The birth weight (BW) are utilized as indicators of the healthy and term newborns. Factor that affects the weight of a newborn are micronutrient intake and family economic status. Folic acid and iron (Fe) were associated with birth weight. Family economic status towards the inability of households in eating conditions that will affect the nutritional status of the pregnant women. The purpose of this study was to analyze the relationship between intake of folic acid, iron (Fe) and family economic status with birth weight. This research method was an analytic observational using a cross-sectional approach. The sample in this study were 114 pregnant women living in Yogyakarta. The data collected, subject characteristic, intake of folic acid and iron and the birth weight. Data analysis used the Fisher exact test with p value <0.05. Statistical test results proved a significant relationship between the intake of folic acid and iron (Fe) with the birth weight (p<0.05). There was no significant relationship between economic status and the birth weight (p>0.05). Pregnant women with adequate folic acid intake, iron intake tended to give birth with normal birth weight. While a good economic status does not necessarily affect the weight of newborns.